Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
[tex]2x^3+x^2-18x-9=x^2(2x+1)-9(2x+1)\\\\=(2x+1)(x^2-9)=(2x+1)(x^2-3^2)\\\\=(2x+1)(x-3)(x+3)[/tex]
[tex]2x^3 + x^2 - 18x - 9=x^2(2x+1)-9(2x+1)=\\ \\=(2x+1)(x^2-9)=(2x+1)(x-3)(x+3)[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.